The Connection between Young Students’ Physical Health and Their Lifestyle - Geske, Rita; Leice, Alevtīna; Miķelsone, Madara; Kudrjavceva, Laila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The goal of this research is to analyze the status of young students’ physical health and its connection with lifestyle. The research participants were 107 Medical College’s 1st year students that formed part of the youth category as it is defined in Latvia, i.e., up until the age of 25. Students’ physical health was evaluated in accordance with Apanasenko’s methods based on investigative anthropometric and functional testing measurements. These measurements included body mass index, vital capacity, strength index, Robinson index and Recovery Heart Rate. Students’ lifestyle habits were determined with the help of questionnaire that included question groups regarding the self-evaluation of health status, health problems and illnesses, eating habits, bad habits, rest and physical activities. During the research, lipid parameters in blood were also measured determining the total cholesterol (TC), high-density lipoprotein (HDL) and low-density lipoprotein (LDL).